GENERALIZED ANALYSIS OF MONOCLONAL ANTIBODIES TO IGE IN THE TREATMENT OF BRONCHIAL ASTHMA IN CHILDREN IN RUSSIAN FEDERATION - T.V. Kulichenko; A.A. Baranov; M.M. Abelevich; E.V. Balashova; E.A. Vishneva; A.N. Galustyan; S.Yu. Elizarova; I.V. Koroleva; A.G. Manvelyan; L.S. Namazova-Baranova; Yu.V. Peshekhonova; E.V. Timofeeva; et al. (Union of pediatricians of Russia, 2011)
The article presents a generalized 2-year Russian experience in the application of monoclonal antibodies to IgE in children and adolescents with severe, resistant to standard treatment of bronchial asthma. Data on 65 patients treated with anti-IgE therapy with omalizumab within more than 6 months period in 6 centers of the Russian Federation from 2007 to 2010 were analyzed. The results of this analysis demonstrate the safety and high clinical effectiveness of anti-IgE-therapy in children and adolescents with severe uncontrolled atopic bronchial asthma. Full control of the disease or marked improvement can be achieved in 73% patients, the effect in most cases significantly increases during the first 6 months of treatment and becomes stable in the future, providing a good quality of life and normal lung function.Key words: bronchial asthma, anti-IgE-therapy, treatment, adolescents, children, quality of life, omalizumab.